2014
DOI: 10.2147/idr.s49229
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomimetics as a new generation of antimicrobial agents: current progress

Abstract: Antibiotic resistance is an increasing public health concern around the world. Rapid increase in the emergence of multidrug-resistant bacteria has been the target of extensive research efforts to develop a novel class of antibiotics. Antimicrobial peptides (AMPs) are small cationic amphiphilic peptides, which play an important role in the defense against bacterial infections through disruption of their membranes. They have been regarded as a potential source of future antibiotics, owing to a remarkable set of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 90 publications
2
60
0
Order By: Relevance
“…This is in agreement with the findings of Kelly et al, who showed that gp63 gene expression is downregulated in Leishmania during the amastigote life stage (38). With recent peptidomimetic technology, a new class of host defense peptides has been developed, optimizing the peptide's antipathogenic activity and overcoming the low in vivo stability of most host defense peptides due to degradation by proteases (39). Strategies to overcome protease sensitivity include the incorporation of the D form, rather than the naturally occurring L form, of amino acids and in addition reversing the sequence and thus the chirality of amino acids in peptidomimetics (designated "RI" for retroinversion from peptides) (8).…”
Section: Discussionsupporting
confidence: 90%
“…This is in agreement with the findings of Kelly et al, who showed that gp63 gene expression is downregulated in Leishmania during the amastigote life stage (38). With recent peptidomimetic technology, a new class of host defense peptides has been developed, optimizing the peptide's antipathogenic activity and overcoming the low in vivo stability of most host defense peptides due to degradation by proteases (39). Strategies to overcome protease sensitivity include the incorporation of the D form, rather than the naturally occurring L form, of amino acids and in addition reversing the sequence and thus the chirality of amino acids in peptidomimetics (designated "RI" for retroinversion from peptides) (8).…”
Section: Discussionsupporting
confidence: 90%
“…Antimicrobial peptide molecules are what have been in use for defense against microbes. But, they have intrinsic drawbacks, such as susceptibility to enzymatic degradation, toxicity, and high production cost 70 . Peptidomimetic methods for creating Antimicrobial peptides have been recently discovered that help in resistance against multidrug resistant bacteria, while overcoming the drawbacks of the already in use, Antimicrobial peptides.…”
Section: Peptidomimetics To Combat Hivmentioning
confidence: 99%
“…Peptidomimetic methods for creating Antimicrobial peptides have been recently discovered that help in resistance against multidrug resistant bacteria, while overcoming the drawbacks of the already in use, Antimicrobial peptides. Hu et al, 71 and Niu et al, 72 reported the development of a new class of peptidomimetics termed -AApeptides‖, and depending on the position of the side, they have been divided into two subclasses: α-AApeptides and γ-AApeptides 73 .…”
Section: Peptidomimetics To Combat Hivmentioning
confidence: 99%
“…Indeed, aminoglycosides and small cationic antimicrobial peptides are naturally occurring antibacterial agents, with the latter class of compounds being regarded as an emerging source of new antimicrobials [84,85]. Furthermore, to overcome some of their drawbacks (e.g., susceptibility of protease-induced cleavage), peptidomimetics are A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 28 currently being explored with some of them in clinical trials [84][85][86]. In addition, it is noteworthy that guanidine-containing compounds including small peptides and peptidomimetics harbouring one or more guanidino or arginine moieties are of immense interest as drugs targeting a variety of disorders and diseases [87].…”
Section: Accepted Manuscriptmentioning
confidence: 99%